Rekognisi Keragaman Budaya dan Multikulturalisme Bhineka Tunggal Ika - Sugeng; Naupal; LG. Saraswati; Abby Gina Boang Manalu (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
This article aims to examine various models and theories of multiculturalism that are applied through recognition politics in several countries. As a pluralistic country, Indonesia has developed a unique process of multiculturalism in accordance with the characteristics of society, history and political system. This study uses the method of library research (library research) which is descriptive qualitative in nature, to elaborate on the fundamental structure and basic principles of recognition politics and multiculturalism which are the central themes of the discussion. The main question discussed in this article is how multiculturalism and the politics of recognition proceed in Indonesia. The results of the study show that the relationship between society and the state is not a given process, but a dynamic and unfinished process of becoming. In this process, Pancasila and Bhineka Tunggal Ika play a role as a social imaginary, which is the cornerstone of building a national identity and developing a more appropriate and moderate multicultural society. By recognizing, appreciating, and promoting art, culture, and the identities of various cultural groups in Indonesia, it is hoped that a more inclusive and harmonious society will be created.